Pembaruan Penyelesaian Perkara Secara Elektronik menurut Perma No. 7 Tahun 2022 Perspektif Asas-Asas Peradilan Agama - Asni, Asni (KALOSARA: Family Law Review, 2024)
This article examines Perma No. 7 of 2022 regarding updating the application of electronic settlement of cases, which was previously regulated in Perma No. 3 of 2018 and Perma No. 1 of 2019. This study specifically examines the development of an electronic case settlement system in Perma No. 7 of 2022 and the problems with its application in the Religious Courts, which are then reviewed from the procedural principles of the Religious Courts. This study applies the normative-empirical legal research method. This research reveals changes in Perma No. 7 of 2022, among other things, regarding the necessity of electronic trials in cases that are registered electronically, and in conditions where the defendant does not agree, the Registrar of the Session will assist the process through PTSP. The developments in the Perma in several parts are in line with the principles of procedural law, in particular the principles of simplicity, speed and low cost. However, on the other hand, it also has the potential to hinder the fulfillment of other principles such as the principle of the obligation to reconcile and trials open to the public. In several religious courts, this Perma has not been fully implemented due to certain constraints such as sending summons or notifications by post.Therefore, the existence of this Perma and the electronic case settlement system in general, need to be continuously studied. In its implementation, the presence of this Perma must be balanced with socialization, strengthening human resources, and developing infrastructure that is evenly distributed to all levels of society.